Prevalence of Myofascial Pain Syndrome and Efficacy of Trigger Point Injection in Patients with Incurable Cancer: A Multicenter, Prospective Observational Study (MyCar Study). Issue 7 (23rd December 2021) - Ishiki, Hiroto; Hasuo, Hideaki; Matsuda, Yoshinobu; Matsuoka, Hiromichi; Hiramoto, Shuji; Higuchi, Masaki; Yoshida, Kohei; Tokoro, Akihiro; Hatano, Yutaka; Hori, Tetsuo; Kinkawa, Junya; Nojima, Masanori
Abstract: Objective: Myofascial pain syndrome (MPS) is caused by overload or disuse of skeletal muscles. Patients with cancer are often forced to restrict their movement or posture for several reasons. The study was conducted to investigate the prevalence and risks of MPS in patients with incurable cancer. The efficacy of trigger point injection (TPI) was also explored. Methods: This was a multicenter, prospective observational study. Patients with incurable cancer who started receiving specialist palliative care were enrolled. We investigated the MPS in this population and accompanying risk factors for restricting body movement. Pre- and post-TPI pain was also evaluated using a Numerical Rating Scale (NRS) in patients who received TPI. The primary outcome was the prevalence of MPS. Results: A total of 101 patients were enrolled from five institutions in Japan. Most of the patients (n = 94, 93.1%) had distant metastases, and half of the patients (50, 49.5%) received anticancer treatment. Thirty-nine (38.6%) patients had MPS lesions at 83 sites. Multivariate analysis revealed that the significant risk factor for MPS was poor Performance Status (PS) (odds ratio 3.26; 95% confidence interval [CI] 1.18–9.02, P = .023). We performed TPI for 40 out of 83 MPS lesions. Mean NRS for MPS before TPI was 7.95, which improved to 4.30 after TPI ( P < .001). Conclusions: MPS was common in patients with incurable cancer and the risk factor identified in this study was poor performance status. TPI could be a treatment option.